2019
DOI: 10.1101/2019.12.18.881334
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exaggerated Cortical Representation of Speech in Older Listeners: Mutual Information Analysis

Abstract: Aging is associated with an exaggerated representation of the speech envelope in auditory cortex. The relationship between this age-related exaggerated response and a listener's ability to understand speech in noise remains an open question. Here, information-theory-based analysis methods are applied to magnetoencephalography (MEG) recordings of human listeners, investigating their cortical responses to continuous speech, using the novel measure of phaselocked mutual information between the speech stimuli and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 67 publications
1
11
1
Order By: Relevance
“…Note that the mutual information method does not need to be applied between stimulus and EEG necessarily, but can also be applied between different EEG signals to get additional insights. This technique has been used by Gross et al (2014), Zan et al (2020), and Kaufeld et al (2020).…”
Section: Methods To Measure Neural Trackingmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that the mutual information method does not need to be applied between stimulus and EEG necessarily, but can also be applied between different EEG signals to get additional insights. This technique has been used by Gross et al (2014), Zan et al (2020), and Kaufeld et al (2020).…”
Section: Methods To Measure Neural Trackingmentioning
confidence: 99%
“…The most common approach to do so is based on linear encoding/decoding models. Other response analysis methods exist, including inter-trial coherence (ITC) (Zion Golumbic et al, 2013; Bourguignon et al, 2020), cross-correlation (Kong et al, 2014; Aiken and Picton, 2008; Petersen et al, 2016), mutual information (Gross et al, 2014; Zan et al, 2020; Kaufeld et al, 2020) and neural networks (Katthi et al, 2020; Accou et al, 2021), but these will not be discussed further.…”
Section: The Neural Tracking Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The enhanced M50 TRF in older adults also agrees with the integration window results above, that the exaggerated representation starts even at early cortical processing stages. Larger early cortical peaks (~50 ms latency) in older adults have been reported using both EEG (McCullagh and Shinn 2013; Roque et al 2019b) and MEG (Brodbeck et al 2018; Zan et al 2020), for both speech in quiet and in noisy conditions. Alain et al (2014) suggested that this increased neural activity may be caused by excitatory and inhibitory imbalance, which is further in agreement with animal studies (McCullagh and Shinn 2013), and is consistent with other studies (Brodbeck et al 2018).…”
Section: Discussionmentioning
confidence: 94%
“…One interesting use case for measures that overcome the problems outlined above is the heavily studied phenomenon of speech envelope tracking as observed in magneto-and electroencephalography (henceforth MEEG to denote both modalities) recordings (Ahissar et al, 2001;Hertrich et al, 2012;Gross et al, 2013;Ding & Simon, 2012;O'Sullivan et al, 2015;Di Liberto et al, 2015;Wöstmann et al, 2017;Brodbeck et al, 2018;Daube et al, 2019;Obleser & Kayser, 2019;Zan et al, 2020;Donhauser & Baillet, 2020). In short, the low-frequency portion of MEEG signals is reliably related to the time varying energy of the speech signal at a certain delay.…”
Section: Introductionmentioning
confidence: 99%